Unpaid Internship in the Development of Indonesian Employment Regulations - Silvia Cahyadi; Gunardi Lie; Moody Rizqy Syailendra (Fakultas Hukum Dehasen, 2023)
To address this issue, some countries have implemented policies governing unpaid internships, including time limits and minimal financial compensation. This aims to protect the rights of young workers and prevent labor exploitation. On the other hand, there are also opinions that companies should be more responsible and value the contributions made by interns by providing reasonable financial incentives. Overall, Unpaid Internship has significant pros and cons. While it can provide valuable opportunities for students or recent graduates, there needs to be regulations and policies that recognize the need for fair financial incentives and increased protection for young workers. In a society that is increasingly moving towards inclusivity and equality, it is important to consider the balance between company interests and workers' rights.